HEMATOLOGICAL PROFILE IN PATIENTS OF CHRONIC KIDNEY DISEASE WITH ITS SEVERITY IN A TERTIARY CARE HOSPITAL, NORTH ODISHA - BEHERA, BIBHU PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Efforts can be made to normalize the hematological parameters and slow the progress of the disease so that the morbidity and mortality in these patients with chronic kidney disease could be effectively reduced. Methods: The observational study was carried out in the Department of General Medicine, Pandit Raghunath Murmu Medical College Hospital, Baripada, between May 2018 and January 2019. Two hundred seventy patients of chronic kidney disease (CKD) above 15 years of age, satisfying the inclusion and exclusion criteria, were included in the study. Results: In our study, 179 (66.30%) were male, and 91 (33.70%) were female with M:F of 1.97:1. The average age of the patients in the study was 55.72±12.77 years. About 42.59 % (115) of the patients were between 46 and 60 years of age. About 35.56% of CKD cases had determined etiology and, 64.44% of cases had unknown etiology. Hemoglobin, RBC, and packed cell volume were significantly lower in the patients with CKD compared to the controls (p=0.0001), and RDW was considerably higher in the patients with CKD compared to the controls (p=0.0001). Microcytic anemia was the most prevalent type of anemia. There was a hugely significant association between the prevalence of thrombocytopenia and the severity of CKD (p=0.006). Conclusion: This study concluded that patients with CKD show abnormal hematological parameters. Evaluation of hematological parameters in these patients helps in classifying the type of anemia, aids in choosing the correct treatment modalities, and decreases mortality.